KOSMOLOGI MELAYU: Studi Pada Arsitektur Masjid Kesultanan Sambas - Lamazi, Lamazi (The Pontianak State Institute of Islamic Studies, 2015)
Cosmology is the science of the universe and discusses the origins of events such as the parts contained in the embodiment of the universe, the Malay’s cosmology contained in the works of art can be seen at the mosque Jami ' of Sambas, namely on the Mihrab, Pulpit, Calligraphy , Foundations, Forms roof, Porch, Door, Window, and Pillar Mosque.